(untitled) (Annals of Medical Research, 2023)
Aim: In recent years, there has been an increase in the frequency of use of food additives and colorants to extend the life of food and to color it. Excessive consumption of these additives can lead to attention deficit hyperactivity disorder and learning disorder, especially in children. Uncontrolled additives whose dosage is not specified can cause an allergic reaction, cause damage to the neurological system and cause cancer. There are not many studies showing the dose-dependent effect of carminic acid. It was aimed to determine the dose-dependent changes of carminic acid, a food additive, in liver, kidney, blood and brain tissues (hippocampus, brain, brain stem) and to investigate the effects of these doses on hyperactivity behaviorally. Materials and Methods: In our study, dose-dependent effects of 500 mg, 1500 mg and 3000 mg carminic acid (CA) used as a colorant in hippocampus, brain, brain stem, liver, kidney and blood samples were investigated. Results: 32 Wistar albino male rats weighing 150-200 g were divided into 4 groups as control, CA-500, CA-1500 and CA-3000. The locomotor activities of the rats were evaluated in the open field test, and their anxiety behaviors were evaluated in the elevated plus maze test. Carminic acid levels in hippocampus, brain, brain stem, liver, kidney and blood were measured by high performance liquid chromatography (HPLC) method. Locomotor activity and anxiety behavior test results of CA-1500 and CA-3000 groups were increased compared to the control group. In the results of HPLC analysis, 500 mg, 1500 mg and 3000 mg doses administered to rats were not detectable in hippocampus, brain and brain stem tissues, while a dose-dependent increase was found in liver, kidney and blood samples (p<0.05). Conclusion: It was concluded that since carminic acid could not cross the blood-brain barrier, it was not detected in hippocampus, brain and brain stem tissues, and increased dose-dependently in peripheral tissues such as liver, kidney and blood. Although it cannot be detected in the brain, it has been observed that hyperactivity, which may increase locomotor activity and anxiety, may lead to behavioral changes.